Right heart reverse remodeling: “facta non verba” - Tommaso Recchioni; Giovanna Manzi; Alexandra Mihai; Francesca Ileana Adamo; Annalisa Caputo; Domenico Filomena; Giorgia Serino; Silvia Papa; Nadia Cedrone; Carmine Dario Vizza; Roberto Badagliacca (International Journal of Cardiology Congenital Heart Disease)
Pulmonary arterial hypertension (PAH) is characterized by pulmonary vascular remodeling and arterial narrowing, leading to a progressive rise in right ventricular (RV) afterload and poor survival outcomes. PAH prognosis largely depends on RV remodeling and function: when the increased afterload exceeds the RV's adaptive capacity, ventricular-arterial uncoupling occurs, ultimately causing right heart failure and death. In this clinical setting the primary treatment goal is to achieve low mortality risk and right heart reverse remodeling (RHRR). Unfortunately, the definition of RHRR vary across studies and imaging modalities (echocardiography or Cardiac Magnetic Resonance). The likelihood of RHRR increases with a significant reduction in pulmonary vascular resistance (PVR) from baseline, ideally by at least 50 %. Evidence supports initial triple therapy, including parenteral prostanoids, as the most effective approach to reduce PVR enough to facilitate RHRR and thus achieve the low-risk status.